Peranan Dewan Kehormatan Penyelenggara Pemilu (DKPP) Dalam Menegakkan Kemandirian, Integritas, dan Kredibilitas Penyelenggara Pemilu Dalam Pemilu Kepala Daerah dan Wakil Kepala Daerah Tahun 2015 - Jejen Fauzi Ridwan; Nur Hidayat Sardini; Muhammad Adnan (Journal of Politic and Government Studies, 2017)
Elections should be held with direct, public, free, and secret principles by anational, permanent and independent Election Commission (KPU). But often the electionis colored by cheating, manipulation and violation. Violations occurring in the GeneralElection already have their own legal framework, including the completion of violationsof the code of conduct of election organizers handled by the General ElectionsAdministrator's Council (DKPP). Settlement of violations is important because itconcerns the election justice system, namely the extent to which violations are resolvedthoroughly. According to the provisions of Law No. 8 of 2015 on Pemilukada heldsimultaneously in 269 regions, consisting of 9 provinces, 224 districts and 36 cities inIndonesia. Therefore in this study will be discussed the role of DKPP which includesmechanisms and strategies undertaken DKPP in the face of Pemilukada 2015.Based on the research results have some conclusions. The mechanism forresolving code violations in DKPP includes complaints administration, administrativeverification administration and material verification, court administration and decisionadministration. DKPP's verdict is final and binding on several categories based on theweight or severity of a violation committed. Election Organizer in Pemilukada 2015 isconsidered to have integrity, it can be seen from number of election organizers examinedby DKPP more that rehabilitated or not proven to violate, compared with provenviolation. DKPP preventive measures to prevent violations of the code of conduct ofelection organizers include three programs, namely general socialization, FGD (FocusGroup Discussion) and special socialization.Some suggestions from the results of this study, that the Election Organizershould comply with the code of conduct of the election organizers, the awareness shouldbe strongly entrenched, for candidate pairs and election participants should not onlymake the election organizers a mere target of anger, but also must always maintain ethicsand norms in competing during the Pemilukada.Keyword : DKPP, mechanism for resolution of code violation, Pemilukada 2015.